Synthesis of Dimethyl (Z)-2-(Ethanimidoylsulfanyl)-2- butenedioate from Dimethyl Acetylendicarboxylate and Thioacetamide - ARJMANDFAR, HAMID; NAMJOU, NAFISEH; RAMAZANI, ALI (Asian Journal of Chemistry, 2010)
Thioacetamide reacts with dimethyl acetylenedicarbo-xylate in acetone to form dimethyl (Z)-2-(ethanimidoyl-sulfanyl)-2-butenedioate. Sodium hydrogen carbonate powder was found to catalyze the reaction in solvent-free conditions at 90ºC in 1 h.